2021
DOI: 10.1094/phyto-05-20-0193-r
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Genetic Architecture of Nonhost Resistance in Barley Using Pathogenically Diverse Puccinia Isolates

Abstract: Barley is an intermediate or near-nonhost to many cereal rust pathogens that infect grasses, making it a highly suitable model to understand the evolution and genetic basis of nonhost resistance (NHR) in plants. To characterise the genetic architecture of NHR in barley, we used the Oregon Wolfe Barley doubled haploid (DH) and Morex x SusPtrit RIL mapping populations. To elicit a wide array of NHR responses, we tested 492 barley accessions and both mapping populations with pathogenically diverse cereal rust iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Hence, a horizontal/race-independent resistance that has the character of nonhost resistance to leaf rust as a host-specific pathogen could be more durable. This nonhost–pathogen interaction was exemplarily described for barley— P. triticina ( Jafary et al., 2008 ; Haghdoust et al., 2021 ) and wheat— Blumeria hordei , P. hordei , and Magnaporthe oryzae ( Delventhal et al., 2017 ). Nonhost interactions result in prehaustorial resistance (phr) and have also been observed in T. monococcum–P.…”
Section: Introductionmentioning
confidence: 86%
“…Hence, a horizontal/race-independent resistance that has the character of nonhost resistance to leaf rust as a host-specific pathogen could be more durable. This nonhost–pathogen interaction was exemplarily described for barley— P. triticina ( Jafary et al., 2008 ; Haghdoust et al., 2021 ) and wheat— Blumeria hordei , P. hordei , and Magnaporthe oryzae ( Delventhal et al., 2017 ). Nonhost interactions result in prehaustorial resistance (phr) and have also been observed in T. monococcum–P.…”
Section: Introductionmentioning
confidence: 86%
“…Hence, a horizontal/race-independent resistance that has the character of nonhost resistance to leaf rust as a host-specific pathogen could be more durable. This nonhost-pathogen interaction was exemplarily described for barley-P. triticina (Jafary et al, 2008;Haghdoust et al, 2021) and wheat-Blumeria hordei, P. hordei, and Magnaporthe oryzae (Delventhal et al, 2017). Nonhost interactions result in prehaustorial resistance (phr) and have also been observed in T. monococcum-P. triticina interactions (Serfling et al 2016;Anker et al 2001;Anker and Niks, 2001).…”
Section: Introductionmentioning
confidence: 87%
“…One common strategy for using near‐hosts to understand NHR is to find intraspecific or interspecific variation in NHR and identify genes underlying the differences through genetic mapping. For example, in a recent report, Haghdoust et al ( 2021 ) tested 492 barley accessions and two mapping populations with pathogenically diverse cereal rust ( Puccinia ) isolates representing distinct formae speciales adapted to different cereal species. The authors found that about 80% of the barley accessions were either immune or near immune to all pathogens tested and identified major quantitative trait loci (QTLs) in barley that may contribute to NHR (Haghdoust et al, 2021 ).…”
Section: Approaches Used To Elucidate Nhr Mechanismsmentioning
confidence: 99%
“…For example, in a recent report, Haghdoust et al ( 2021 ) tested 492 barley accessions and two mapping populations with pathogenically diverse cereal rust ( Puccinia ) isolates representing distinct formae speciales adapted to different cereal species. The authors found that about 80% of the barley accessions were either immune or near immune to all pathogens tested and identified major quantitative trait loci (QTLs) in barley that may contribute to NHR (Haghdoust et al, 2021 ). These observations support the notion that there is a continuum between NHR and host resistance, and in some cases the resistance phenotypes are quantitative traits (Bettgenhaeuser et al, 2014 ).…”
Section: Approaches Used To Elucidate Nhr Mechanismsmentioning
confidence: 99%